Wear-resistant impermeable recycled asphalt and method for preparing same
Patent Information
- Application Number
- CN202610811316.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-05
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2046-06-05
AI Technical Summary
现有再生沥青在耐磨性、抗渗性、低温性能和高温稳定性方面存在不足,难以通过单一或简单复配的纳米材料、聚合物或纤维改性实现全面提升。
A composite modification system is adopted, including nano-silica-graphene composite material, SBS-SBR composite polymer modifier, basalt fiber and organosilicon waterproofing agent. Through interface synergy, structural nesting and functional complementarity, a cross-scale synergistic modification system is formed to improve the comprehensive performance of recycled asphalt.
It significantly improves the wear resistance, impermeability, low-temperature performance and high-temperature stability of recycled asphalt, extends the service life of the pavement, and increases the utilization rate of RAP.
Smart Images

Figure REF-OBJ-1780657361380-000001
Abstract
Description
Technical Field
[0001] This invention belongs to the field of road engineering materials technology, specifically relating to a wear-resistant and impermeable recycled asphalt and its preparation method. Background Technology
[0002] With the rapid development of highway construction in my country, the total mileage of asphalt pavement has exceeded 5 million kilometers. However, a large number of asphalt pavements will experience varying degrees of damage after 5-10 years of use, generating a large amount of waste asphalt mixture (RAP). Recycled asphalt technology is an effective way to recycle and reuse the old asphalt in RAP. By adding recycling agents and new asphalt, the old asphalt can be restored to its road performance. However, traditional recycled asphalt has the following main problems: 1. Poor wear resistance: During long-term use, old asphalt ages, the asphalt content increases, and the content of gum and oil decreases, causing the asphalt to harden and become brittle, reducing its adhesion to aggregates. Under vehicle loads, the road surface is prone to wear, loosening and other defects.
[0003] 2. Insufficient impermeability: Recycled asphalt mixtures have many voids, which allow water to easily seep in, reducing the interfacial adhesion between asphalt and aggregates. Under freeze-thaw cycles, the road surface will develop potholes, spalling, and other damage, seriously affecting the service life of the road surface.
[0004] 3. Poor low-temperature performance: Recycled asphalt has poor low-temperature ductility and is prone to cracking in cold regions.
[0005] 4. High-temperature stability needs to be improved: Recycled asphalt is prone to softening at high temperatures, leading to rutting on the road surface.
[0006] Existing technologies mostly use single nanomaterials, single polymers, or single fibers for modification. Although they can improve one or two properties, it is difficult to achieve comprehensive optimization of wear resistance, impermeability, low-temperature crack resistance, and high-temperature stability at the same time. Moreover, when multiple components are simply compounded, there is a lack of clear synergistic mechanism between the components, which can easily lead to mutual restriction of performance (such as nano-modification alone reducing the low-temperature ductility of asphalt, and polymer modification alone being insufficient in high-temperature rutting resistance), and thus failing to achieve the expected comprehensive modification effect.
[0007] Therefore, developing a recycled asphalt that simultaneously possesses excellent wear resistance, impermeability, low-temperature performance, and high-temperature stability is of great significance for improving the service life of recycled asphalt pavements and promoting the resource utilization of RAP. Summary of the Invention
[0008] The purpose of this invention is to overcome the shortcomings of the prior art and provide a wear-resistant and impermeable recycled asphalt and its preparation method. This recycled asphalt, through the synergistic effect of the composite modification system, significantly improves wear resistance, impermeability, low-temperature performance and high-temperature stability, and has broad application prospects.
[0009] The objective of this invention can be achieved through the following technical solutions: A wear-resistant and impermeable recycled asphalt is composed of the following components in parts by weight: Recycled bitumen: 60-80 parts Base asphalt: 20-40 parts Composite nano-modifier: 3-8 parts Composite polymer modifier: 4-10 parts Basalt fiber: 1-3 parts Silicone waterproofing agent: 0.5-2 parts Compatibilizer: 0.3-1 part Anti-aging agent: 0.2-0.8 parts As a preferred embodiment of the present invention, the composite nano-modifier is a nano-silica-graphene composite material, wherein the mass ratio of nano-silica to graphene is (3-5):1.
[0010] As a preferred embodiment of the present invention, the composite polymer modifier is a mixture of styrene-butadiene-styrene block copolymer (SBS) and styrene-butadiene rubber (SBR), wherein the mass ratio of SBS to SBR is (2-4):1.
[0011] As a preferred embodiment of the present invention, the basalt fiber has a length of 6-12 mm and a diameter of 10-15 μm.
[0012] As a preferred embodiment of the present invention, the organosilicon waterproofing agent is one or more of sodium methylsilicate, sodium ethylsilicate, or methyltriethoxysilane.
[0013] As a preferred embodiment of the present invention, the compatibilizer is maleic anhydride-grafted polyethylene (PE-g-MAH) or maleic anhydride-grafted polypropylene (PP-g-MAH).
[0014] As a preferred embodiment of the present invention, the anti-aging agent is a mixture of hindered phenolic antioxidant 1010 and ultraviolet absorber UV-327, wherein the mass ratio of antioxidant 1010 to ultraviolet absorber UV-327 is (1-2):1.
[0015] As a preferred technical solution of the present invention, the recycled asphalt is extracted from waste asphalt mixture (RAP) and has a penetration (25°C) of 20-40 (0.1 mm), a softening point of 55-70°C, and a ductility (5°C) of less than 10 cm. The base asphalt is No. 70 Grade A road petroleum asphalt, with a penetration (25℃) of 60-80 (0.1mm), a softening point of 44-54℃, and a ductility (5℃) greater than 20cm.
[0016] A method for preparing the above-mentioned wear-resistant and impermeable recycled asphalt includes the following steps: a. Heat the recycled asphalt to 130-140℃, keep it at that temperature and stir for 30-45 minutes until it is completely melted; b. Add base asphalt to the molten recycled asphalt, heat to 150-160℃, stir for 20-30 minutes, and mix evenly; c. Add composite nano-modifier and compatibilizer to the above mixture, and shear at high speed at 150-160℃ for 30-45 min, with a shear rate of 4000-6000 r / min; d. Add the composite polymer modifier and continue high-speed shearing for 45-60 minutes at a shear rate of 4000-6000 r / min; e. Add basalt fiber and stir at 150-160℃ for 20-30 minutes at a stirring rate of 1000-1500 r / min; f. Add silicone waterproofing agent and anti-aging agent, stir at 140-150℃ for 15-20 minutes, and the stirring rate is 800-1000 r / min; g. The resulting mixture is developed at 140-150℃ for 1-2 hours to obtain wear-resistant and impermeable recycled asphalt.
[0017] As a preferred embodiment of the present invention, the high-speed shearing time in step 3 is 35-40 min and the shearing rate is 5000 r / min; the high-speed shearing time in step 4 is 50-55 min and the shearing rate is 5000 r / min.
[0018] The beneficial effects of this invention are: 1. This invention overcomes the limitations of traditional single / two-component modification, constructing a cross-scale synergistic modification system of "nano-microscopic reinforcement - polymer mesoscopic toughening - fiber mesoscopic load-bearing - waterproofing agent functional protection". The components are not simply superimposed, but generate a synergistic effect of "1+1+1+1>4" through interfacial interactions, structural nesting, and functional complementarity, as detailed below: ① Nano-polymer interface synergy: resolving the contradiction of "strength and toughness being mutually exclusive". The hydroxyl groups on the surface of nano-silica can undergo physical adsorption and chemical entanglement with the double bonds in the SBS and SBR molecular chains, improving the uniformity of polymer dispersion in asphalt. Simultaneously, the polymer molecular chains encapsulate the nanoparticles, forming a "polymer shell-nanocore" structure, effectively inhibiting the aggregation of nano-silica and graphene. The two-dimensional sheet structure of graphene can serve as "crosslinking points" for the polymer molecular chains, making the elastic network formed by SBS-SBR more compact and stable.
[0019] Single nano-modification can only increase the hardness of asphalt but reduce its low-temperature ductility, while single polymer modification can only increase toughness but lacks high-temperature stability. When the two are combined, the softening point of recycled asphalt is increased by 4-7℃ compared with single polymer modification, and the low-temperature bending failure strain is increased by 39%-52% compared with single nano-modification, achieving a simultaneous improvement in high-temperature strength and low-temperature toughness.
[0020] ② Fiber-matrix structure synergy: Constructing a dual reinforcement network at the "micro-scale" and "meso-scale" levels. Basalt fibers are randomly distributed within the asphalt matrix, forming a microscopic three-dimensional fiber network that is nested within a microscopic reinforcing network formed by nano-polymers. The nano-network is responsible for dispersing the micro-stress generated by vehicle loads and preventing the initiation of microcracks; the fiber network, through bridging, bears the macroscopic load and prevents microcracks from propagating into macroscopic cracks.
[0021] Meanwhile, nano-silica-graphene can fill the interfacial voids between basalt fibers and the asphalt matrix, improving interfacial bonding strength; organosilicon waterproofing agents can form a hydrophobic film on the fiber surface, preventing moisture from penetrating the interface and causing bonding failure. Single fiber modification can only improve mechanical strength, but when combined with a nano-polymer matrix, wear resistance and crack resistance are significantly enhanced.
[0022] ③ Synergistic Waterproofing and Enhanced Functions: Forming a dual anti-seepage system of "surface hydrophobicity + internal sealing". Organosilicon waterproofing agents not only form a dense hydrophobic film on the asphalt surface, reducing surface energy and preventing water adhesion, but also penetrate into the capillary channels inside the asphalt. Together with the physical filling effect of nano-silica-graphene, they cut off the penetration path of water.
[0023] A single waterproofing agent can only reduce surface water seepage, but cannot seal internal capillary channels; a single nanofiller can only seal large pores, but cannot prevent the diffusion of water molecules. When the two are used together, water stability is greatly improved.
[0024] 2. Through the synergistic effect of the above three layers, this invention achieves for the first time a comprehensive and simultaneous improvement in the wear resistance, impermeability, low-temperature crack resistance and high-temperature stability of recycled asphalt, solving the problem of "mutual constraint of performance" in traditional modification technology. This is an effect that cannot be achieved by any single or two-component modification.
[0025] 3. The addition of anti-aging agents can effectively inhibit the thermal and photo-oxidative aging of asphalt, and work together with the quaternary synergistic system to effectively extend the service life of recycled asphalt pavement.
[0026] 4. The preparation method of the present invention is simple, requires no special equipment, is easy to industrialize, and greatly improves the utilization rate of RAP, thus having good economic and environmental benefits. Detailed Implementation
[0027] To further illustrate the technical means and effects of the present invention in achieving its intended purpose, the following detailed description of the specific implementation methods, structures, features, and effects of the present invention, in conjunction with embodiments, is provided below.
[0028] Example 1
[0029] The wear-resistant and impermeable recycled asphalt of this embodiment is composed of the following components in parts by weight: Recycled bitumen: 70 parts Base asphalt: 30 parts Composite nano-modifier: 5 parts (nano silica: graphene = 4:1) Composite polymer modifier: 7 parts (SBS:SBR=3:1) Basalt fiber: 2 parts (9mm in length, 12μm in diameter) Organosilicon waterproofing agent: 1.2 parts (sodium methylsilicate) Compatibilizer: 0.6 parts (PE-g-MAH) Anti-aging agent: 0.5 parts (antioxidant 1010:UV-327 = 1.5:1) Preparation of composite nano-modifiers (nano-silica-graphene composite materials) 1. Select oleophilic nano-silica with a particle size of 20nm and single-layer powdered graphene, and dry them in a vacuum drying oven at 60℃ for 4 hours to remove the adsorbed moisture inside the powder and avoid the problems of bubbles and uneven dispersion in the subsequent asphalt processing. 2. Weigh the dried nano-silica and graphene at a mass ratio of 4:1, add them together to anhydrous ethanol dispersion medium, control the solid-liquid ratio at 1:10, and use an ultrasonic disperser to ultrasonically treat for 40 minutes with an ultrasonic power of 300W to ensure that the two nano-powders are uniformly mixed without agglomeration or clumping. 3. Transfer the well-dispersed mixture to a rotary evaporator and remove the anhydrous ethanol solvent by rotary evaporation under reduced pressure at 65°C. Then, place the solid powder in a vacuum oven at 80°C and dry for 6 hours to completely remove the residual solvent. 4. After drying, the nano-silica-graphene composite nano-modifier is obtained by ball milling for 30 minutes using a planetary ball mill and passing it through a 200-mesh standard sieve. It is then sealed and stored for later use.
[0030] Preparation of composite polymer modifier (SBS+SBR compound system) 1. Linear SBS (grade YH-792) and powdered styrene-butadiene rubber SBR (grade 1502) are selected to ensure compatibility between the two polymers and the asphalt matrix; 2. Weigh SBS granules and SBR powder at a mass ratio of 3:1, and stir them at room temperature for 15 minutes using a low-speed stirring device at a stirring rate of 300 r / min to achieve macroscopic uniform mixing of the two polymers. 3. After premixing, seal and store in a moisture-proof environment to prevent the polymer from absorbing moisture and affecting the subsequent asphalt shear modification effect. Use as needed.
[0031] Preparation method: 1. Heat the recycled asphalt to 135℃, keep it at that temperature and stir for 35 minutes until it is completely melted; 2. Add base asphalt to the molten recycled asphalt, heat to 155℃, stir for 25 minutes, and mix thoroughly; 3. Add the composite nano-modifier and compatibilizer to the above mixture, and shear at high speed at 155℃ for 35 min, with a shear rate of 5000 r / min; 4. Add the composite polymer modifier and continue high-speed shearing for 50 minutes at a shear rate of 5000 r / min; 5. Add basalt fiber and stir at 155℃ for 25 minutes at a stirring rate of 1200 r / min; 6. Add silicone waterproofing agent and anti-aging agent, stir at 145℃ for 18 minutes, stirring rate is 900 r / min; 7. The resulting mixture is allowed to mature at 145℃ for 1.5 hours to obtain wear-resistant and impermeable recycled asphalt.
[0032] Example 2
[0033] The wear-resistant and impermeable recycled asphalt of this embodiment is composed of the following components in parts by weight: Recycled bitumen: 60 parts Base asphalt: 40 parts Composite nano-modifier: 3 parts (nano silica: graphene = 3:1) Composite polymer modifier: 4 parts (SBS:SBR=2:1) Basalt fiber: 1 part (6 mm in length, 10 μm in diameter) Organosilicon waterproofing agent: 0.5 parts (sodium ethylsilicate) Compatibilizer: 0.3 parts (PP-g-MAH) Anti-aging agent: 0.2 parts (antioxidant 1010:UV-327 = 1:1) Preparation of composite nano-modifiers (nano-silica-graphene composite materials) 1. Same as in Example 1, nano-silica and graphene were vacuum dried at 60°C for 4 hours; 2. Weigh the two nanoparticles at a mass ratio of 3:1, add anhydrous ethanol to prepare a dispersion with a solid-liquid ratio of 1:10, and ultrasonically disperse at 300W for 35 minutes. Solvent was removed by rotary evaporation under reduced pressure at 3.65℃, followed by vacuum drying at 80℃ for 6 hours, ball milling in a planetary ball mill for 25 minutes, and passing through a 200-mesh sieve to obtain the composite nano-modifier.
[0034] Preparation of composite polymer modifier (SBS+SBR compound system) 1. Same as in Example 1, using the same grade of SBS and SBR raw materials; 2. Weigh SBS and SBR at a mass ratio of 2:1, stir at a low speed of 300r / min for 15min, and seal and store after macroscopic mixing is uniform.
[0035] Preparation method: 1. Heat the recycled asphalt to 130℃, keep it at that temperature and stir for 30 minutes until it is completely melted; 2. Add base asphalt to the molten recycled asphalt, heat to 150℃, stir for 20 minutes, and mix thoroughly; 3. Add the composite nano-modifier and compatibilizer to the above mixture, and shear at high speed at 150℃ for 30 min, with a shear rate of 4000 r / min; 4. Add the composite polymer modifier and continue high-speed shearing for 45 minutes at a shear rate of 4000 r / min; 5. Add basalt fiber and stir at 150℃ for 20 minutes at a stirring rate of 1000 r / min; 6. Add silicone waterproofing agent and anti-aging agent, stir at 140℃ for 15 minutes, stirring rate is 800 r / min; 7. The resulting mixture is developed at 140℃ for 1 hour to obtain wear-resistant and impermeable recycled asphalt.
[0036] Example 3
[0037] The wear-resistant and impermeable recycled asphalt of this embodiment is composed of the following components in parts by weight: Recycled bitumen: 80 parts Base asphalt: 20 parts Composite nano-modifier: 8 parts (nano silica: graphene = 5:1) Composite polymer modifier: 10 parts (SBS:SBR=4:1) Basalt fiber: 3 parts (12mm in length, 15μm in diameter) Organosilicon waterproofing agent: 2 parts (methyltriethoxysilane) Compatibilizer: 1 part (PE-g-MAH) Anti-aging agent: 0.8 parts (antioxidant 1010:UV-327 = 2:1) Preparation of composite nano-modifiers (nano-silica-graphene composite materials) 1. Nano-silica and graphene are vacuum dried at 60℃ for 4 hours to remove adsorbed moisture; 2. Mix the powder according to a mass ratio of 5:1 and a solid-liquid ratio of 1:10, and ultrasonically disperse at 300W for 45 minutes to enhance the dispersion effect of the high proportion of nano-silica system and prevent powder agglomeration. 3. The rotary evaporation and vacuum drying processes are consistent with the previous two examples. After ball milling for 35 minutes, the product is passed through a 200-mesh sieve for later use.
[0038] Preparation of composite polymer modifier (SBS+SBR compound system) 1. Use the same polymer raw materials as in the aforementioned examples to ensure uniqueness of variables; 2. Weigh SBS and SBR at a mass ratio of 4:1, stir at 300 rpm for 15 minutes, mix thoroughly, and then seal and store in a moisture-proof container.
[0039] Preparation method: 1. Heat the recycled asphalt to 140℃, keep it at that temperature and stir for 45 minutes until it is completely melted; 2. Add base asphalt to the molten recycled asphalt, heat to 160℃, stir for 30 minutes, and mix thoroughly; 3. Add composite nano-modifier and compatibilizer to the above mixture, and shear at high speed at 160℃ for 45 min, with a shear rate of 6000 r / min; 4. Add the composite polymer modifier and continue high-speed shearing for 60 minutes at a shear rate of 6000 r / min; 5. Add basalt fiber and stir at 160℃ for 30 minutes at a stirring rate of 1500 r / min; 6. Add silicone waterproofing agent and anti-aging agent, stir at 150℃ for 20 minutes at a stirring rate of 1000 r / min; 7. The resulting mixture is developed at 150℃ for 2 hours to obtain wear-resistant and impermeable recycled asphalt.
[0040] Comparative Example 1 The difference between this comparative example and Example 1 is that no composite nano-modifier is added, while the remaining components and preparation methods are the same as in Example 1.
[0041] Comparative Example 2 The difference between this comparative example and Example 1 is that the composite nano-modifier is only nano-silica, and the amount used is 5 parts. The other components and preparation methods are the same as in Example 1.
[0042] Comparative Example 3 The difference between this comparative example and Example 1 is that the composite nanomodifier is only graphene, and the amount used is 5 parts. The other components and preparation methods are the same as in Example 1.
[0043] Comparative Example 4 The difference between this comparative example and Example 1 is that basalt fiber is not added, while the remaining components and preparation methods are the same as in Example 1.
[0044] Comparative Example 5 The difference between this comparative example and Example 1 is that glass fiber is used instead of basalt fiber, and the amount is 2 parts. The remaining components and preparation methods are the same as in Example 1.
[0045] Comparative Example 6 The difference between this comparative example and Example 1 is that no silicone waterproofing agent is added, while the remaining components and preparation methods are the same as in Example 1.
[0046] Comparative Example 7 The difference between this comparative example and Example 1 is that an acrylic waterproofing agent is used instead of a silicone waterproofing agent, and the amount used is 1.2 parts. The remaining components and preparation methods are the same as in Example 1.
[0047] Comparative Example 8 The difference between this comparative example and Example 1 is that the composite polymer modifier is only SBS, and the amount used is 7 parts. The other components and preparation methods are the same as in Example 1.
[0048] Comparative Example 9 The difference between this comparative example and Example 1 is that the composite polymer modifier is only SBR, and the amount used is 7 parts. The other components and preparation methods are the same as in Example 1.
[0049] Comparative Example 10 The difference between this comparative example and Example 1 is that no compatibilizer is added, while the remaining components and preparation methods are the same as in Example 1.
[0050] Performance testing The recycled asphalt prepared in Examples 1-3 and Comparative Examples 1-10 were tested for performance according to the following standards: Penetration (25℃): Determined according to GB / T4509-2010 "Asphalt Penetration Test Method"; Softening point: Determined according to GB / T4507-2014 "Asphalt Softening Point Determination Method - Ring and Ball Method"; Ductility (5℃): Determined according to GB / T4508-2025 "Asphalt Ductility Test Method"; Marshall stability and flow value: determined according to JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering"; Dynamic stability (60℃): determined according to JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering"; Freeze-thaw splitting strength ratio: determined according to JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering"; Permeability coefficient: determined according to JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering"; Kentucky spillage loss: determined according to JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering"; Low-temperature bending test failure strain: determined in accordance with JTGE20-2011 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering".
[0051] The test results are shown in the table below: Results Analysis The above test results show that: Synergistic effect of composite nano-modifiers: Example 1 exhibited a dynamic stability of 4850 cycles / mm, a Kentenberg scattering loss of 4.2%, and a permeability coefficient of 35 mL / min; while Comparative Example 1 (without composite nano-modifier) showed a dynamic stability of only 2600 cycles / mm, a Kentenberg scattering loss as high as 12.5%, and a permeability coefficient of 120 mL / min. The performance of Comparative Example 2 (with only nano-silica) and Comparative Example 3 (with only graphene) was also significantly lower than that of Example 1. This indicates that nano-silica and graphene have a significant synergistic effect, simultaneously improving the wear resistance, impermeability, and high-temperature stability of recycled asphalt.
[0052] The reinforcing effect of basalt fiber: Comparative Example 4 (without basalt fiber) showed a Marshall stability of 12.8 kN and a Kentenberg scattering loss of 7.6%, significantly lower than Example 1. Comparative Example 5 (using glass fiber instead of basalt fiber) also showed slightly lower performance than Example 1. This indicates that basalt fiber can effectively enhance the mechanical properties and abrasion resistance of recycled asphalt.
[0053] The impermeability of silicone waterproofing agents: Comparative Example 6 (without silicone waterproofing agent) had a water permeability coefficient as high as 110 mL / min, and a freeze-thaw splitting strength ratio of only 80%, far lower than Example 1. Comparative Example 7 (using acrylic waterproofing agent instead of silicone waterproofing agent) had a water permeability coefficient of 80 mL / min, also significantly higher than Example 1. This indicates that silicone waterproofing agents can significantly improve the impermeability and water stability of recycled asphalt.
[0054] Synergistic effect of composite polymer modifiers: The low-temperature ductility and low-temperature flexural failure strain of Comparative Example 8 (SBS only) and Comparative Example 9 (SBR only) were lower than those of Example 1. This indicates that the combined use of SBS and SBR can better improve the low-temperature performance of recycled asphalt.
[0055] The role of compatibilizers: The properties of Comparative Example 10 (without compatibilizer) were significantly lower than those of Example 1. This indicates that compatibilizers can improve the compatibility between components and enhance the modification effect.
[0056] A comprehensive comparison of the performance data of all embodiments and comparative examples reveals that: All comparative examples lacking a certain component had at least one core performance that did not reach the optimal level: Comparative Example 1 had severely insufficient high-temperature stability and wear resistance; Comparative Example 4 had significantly reduced mechanical strength and wear resistance; Comparative Example 6 had extremely poor impermeability and water stability; and Comparative Examples 8 and 9 had insufficient low-temperature crack resistance.
[0057] No two- or three-component compound can simultaneously meet all four performance requirements: for example, the "nano + polymer" compound (Comparative Example 4) can improve high and low temperature performance, but its wear resistance and impermeability are insufficient; the "nano + fiber + polymer" compound (Comparative Example 6) can improve mechanical and high and low temperature performance, but its impermeability and water stability are still not up to standard.
[0058] Only the complete quaternary system of Examples 1-3 simultaneously achieved optimal performance in all aspects, including dynamic stability > 4000 cycles / mm (high temperature), low temperature bending failure strain > 2800με (low temperature), Kentenberg scattering loss < 6% (wear resistance), and water permeability coefficient < 50mL / min (water resistance). This fully demonstrates the necessity and uniqueness of using the four components in combination, which cannot be achieved by simply mixing the individual components.
[0059] This invention utilizes the synergistic effect of composite nano-modifiers, composite polymer modifiers, basalt fibers, and organosilicon waterproofing agents to prepare a recycled asphalt that simultaneously possesses excellent wear resistance, impermeability, low-temperature performance, and high-temperature stability.
[0060] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A wear-resistant and impermeable recycled asphalt, characterized in that, It consists of the following components in parts by weight: Recycled bitumen: 60-80 parts Base asphalt: 20-40 parts Composite nano-modifier: 3-8 parts Composite polymer modifier: 4-10 parts Basalt fiber: 1-3 parts Silicone waterproofing agent: 0.5-2 parts Compatibilizer: 0.3-1 part Anti-aging agent: 0.2-0.8 parts; The composite nano-modifier is a nano-silica-graphene composite material, wherein the mass ratio of nano-silica to graphene is (3-5):1; The composite polymer modifier is a mixture of styrene-butadiene-styrene block copolymer (SBS) and styrene-butadiene rubber (SBR), wherein the mass ratio of SBS to SBR is (2-4):1; The anti-aging agent is a mixture of hindered phenolic antioxidant 1010 and ultraviolet absorber UV-327, wherein the mass ratio of antioxidant 1010 to ultraviolet absorber UV-327 is (1-2):
1. The recycled asphalt is extracted from waste asphalt mixtures, with a penetration of 20-40 (0.1 mm) at 25°C, a softening point of 55-70°C, and a ductility of less than 10 cm at 5°C. The base asphalt is No. 70 Grade A road petroleum asphalt, with a penetration of 60-80 (0.1 mm) at 25℃; a softening point of 44-54℃; and a ductility greater than 20 cm at 5℃.
2. The wear-resistant and impermeable recycled asphalt according to claim 1, characterized in that, The basalt fibers are 6-12 mm in length and 10-15 μm in diameter.
3. The wear-resistant and impermeable recycled asphalt according to claim 1, characterized in that, The organosilicon waterproofing agent is one or more of sodium methylsilicate, sodium ethylsilicate, or methyltriethoxysilane.
4. The wear-resistant and impermeable recycled asphalt according to claim 1, characterized in that, The compatibilizer is maleic anhydride-grafted polyethylene (PE-g-MAH) or maleic anhydride-grafted polypropylene (PP-g-MAH).
5. A method for preparing wear-resistant and impermeable recycled asphalt as described in any one of claims 1-4, characterized in that, Includes the following steps: a. Heat the recycled asphalt to 130-140℃, keep it at that temperature and stir for 30-45 minutes until it is completely melted; b. Add base asphalt to the molten recycled asphalt, heat to 150-160℃, stir for 20-30 minutes, and mix evenly; c. Add composite nano-modifier and compatibilizer to the above mixture, and shear at high speed at 150-160℃ for 30-45 min, with a shear rate of 4000-6000 r / min; d. Add the composite polymer modifier and continue high-speed shearing for 45-60 minutes at a shear rate of 4000-6000 r / min; e. Add basalt fiber and stir at 150-160℃ for 20-30 minutes at a stirring rate of 1000-1500 r / min; f. Add silicone waterproofing agent and anti-aging agent, stir at 140-150℃ for 15-20 minutes, and the stirring rate is 800-1000 r / min; g. The resulting mixture is developed at 140-150℃ for 1-2 hours to obtain wear-resistant and impermeable recycled asphalt.
6. The preparation method according to claim 5, characterized in that, In step c, the high-speed shearing time is 35-40 min, and the shearing rate is 5000 r / min; in step d, the high-speed shearing time is 50-55 min, and the shearing rate is 5000 r / min.
Citation Information
Patent Citations
High-performance warm-mixed special asphalt based on hot in-place recycling and mixture of high-performance warm-mixed special asphalt
CN114806200A
Method for recycling, enhancing and reusing waste pavement asphalt
CN120699447A
